Skrining Tekanan Darah Berbasis Masyarakat sebagai Data Epidemiologi untuk Peningkatan Pelayanan Kesehatan - Este Latifahanun; Rokhayati; Safirina Aulia Rahmi; Awaluddin; Sarif Febriandi; Afwa Aulia Rahma (Journal of Excellence Humanities and Religiosity, 2026)
Non-communicable diseases (NCDs) are chronic, long-lasting diseases caused by genetic, physiological, environmental, and behavioral factors. The increasing prevalence of hypertension makes community service programs focused on early screening and preventive education crucial. The implementation method consists of three stages: preparation, implementation, and evaluation. Preparation includes coordination with various parties; implementation includes blood pressure measurements and brief education about hypertension. Evaluation also includes input from activity participants and the activity team obtained after community-based blood pressure screening. The results of the activity indicated that the majority of respondents were in the normal blood pressure category (44.4%), followed by prehypertension (37.8%), while respondents with stage I and stage II hypertension accounted for 12.2% and 5.6%, respectively. Risk factors frequently encountered during the education program were lack of physical activity, high-salt food consumption, and smoking habits among some male participants.